Palladium-Catalyzed Cross-Coupling between 8-Substituted 6-Thiophenylpurines and Boronic Acids - Vabre, Roxane; Couradin, Julien; Naud-Martin, Delphine; Legraverend, Michel; Piguel, Sandrine (Synthesis, 2014)
A palladium(II)-catalyzed, copper(I)-mediated Liebeskind–Srogl cross-coupling for the C-6 arylation/alkenylation on purine scaffold is reported. Various boronic acids reacted readily with 8-substituted 6-thiophenylpurines.
Keywords: purine; cross-coupling; sulfur; copper; palladium